Impact of a local ordinance banning tobacco sales to minors. - Hinds, M W (1992)
Most addictions to tobacco begin when a person is younger than age 18. Although the sale of tobacco to minors is illegal in most jurisdictions, there is often little enforcement of these laws, and minors can usually purchase tobacco easily. The impact of a local ordinance designed to prevent tobacco sales to minors was assessed by surveys of 10th grade students before and after the implementation of the ordinance. Tobacco use declined from 25.3 percent to 19.7 percent overall, with a significant (P = 0.004) decline from 26.4 percent to 11.5 percent among girls. There was also a significant (P = 0.008) increase from 29.3 percent to 61.5 percent in the proportion of students reporting they were asked for proof of age when they attempted to purchase tobacco. Local ordinances may be an effective tool for reducing tobacco use by adolescents.